Design of chain pillars for deep longwall workings in indian geo-mining conditions - Yadav, Ajeet (IIT(BHU) Varanasi, 2022)
Abstract is available in the content.
Keywords: Design of chain pillars; deep longwall workings; in Indian geo-mining conditions